Respuesta :

Answer:

x = 5 ;  y = - 3

Step-by-step explanation:

2x - 13 = y

2x - y =13   --------------------(i)

-3x + 2y = -21 ----------------(ii)

(i)*2   ===>    4x - 2y = 26

(ii)      ===>   -3x + 2y = -21

add    ==>              x   = 5

When we are adding, -2y and 2y gives 0 or cancelled. 4x and -3x gives 1x; 26 and -21 --> different sign so subtract and put the bigger number sign. so it gives 5.

substitute x = 5 in equ (i)

2*5 - y = 13

10 - y = 13

-y  = 13 -10

y = 3

y = -3

ACCESS MORE